Trauma Volume and Performance of a regional Trauma Center in Korea: Initial 5-year analysis - Byungchul Yu; Giljae Lee; Min A Lee; Kangkook Choi; Sungyoul Hyun; Yangbin Jeon; Yong-Cheol Yoon; Jungnam Lee (Journal of Trauma and Injury)
Purpose We aimed to evaluate the trauma volume and performance indicators during the first 5-year period of operation in a single regional trauma center. Methods We analyzed prospectively collected data from the Korean Trauma Data Bank for a single regional trauma center between January 2014 and December 2018. More than 250 variables were analyzed. We calculated the predicted survival rates using the trauma and injury severity score (TRISS) method. Results In total, there were 16,103 trauma admissions during the first 5 years; trauma activation was performed in 5,105 of these cases. Over 70% of the patients were men, and most of the admitted patients were within the age groups of 55–59 years for men and 75–79 years for women. Analyses were performed considering two patient groups: the total patient group and the group of those with severe trauma (injury severity score [ISS] >15). The median ISS, revised trauma score, and TRISS of the two groups were 5 (interquartile range [IQR] 4–10), 22 (IQR 17–27), and 7.6±0.99 and 6.74±1.9, 0.95±0.13, 0.81±2.67, respectively. Of the total patient group, 801 patients (5%) died in the hospital, whereas of the group of patients with ISS >15, 526 (19.5%) died. The direct transportation of patients to the regional trauma center increased year by year. The emergency room stay time and time to entering the operating room showed a decrease until 2017; however, these parameters increased again in 2018. Conclusions The trauma volume in the regional trauma center is appropriate, and some improvements could be observed after its establishment. However, performance indicators reveal the prematurity of the trauma center and its potential for further improvements. Moreover, the development of a national trauma system, beyond regional trauma centers, is required.